A fatal case of disseminated aspergillosis caused by a non-sporulating strain of Aspergillus fumigatus. Issue 9 (27th August 2004) - Callister, M E; Griffiths, M J; Nicholson, A G; Leonard, A; Johnson, E M; Polkey, M I; Kerr, J R
Abstract : This report describes the case of a 38 year old pregnant woman with fatal disseminated aspergillosis and multiorgan failure, which was preceded by a long history of allergic bronchopulmonary aspergillosis. Postmortem revealed massive infarction and abscess formation in both lungs. Histology revealed a focal granulomatous response. Fungal infiltration with areas of necrosis were also seen in the liver, spleen, and paratracheal, mediastinal, para-aortic, and hilar lymph nodes. Culture of tissue samples produced a non-sporulating, beige coloured fungus that developed green pigmentation only after three weeks of incubation. Nucleotide sequencing of the D1–D2 region of the large ribosomal subunit revealed 100% homology with Aspergillus fumigatus . Minimum inhibitory concentrations for amphotericin B and itraconazole were both 0.25 mg/litre (susceptible). Further work is urgently required to determine the prevalence of such non-sporulating strains and their relevance to clinical infection.